2016
DOI: 10.1155/2016/2313714
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Cervical Polyneuropathies following Concurrent Bortezomib, Cetuximab, and Radiotherapy for Head and Neck Cancer

Abstract: We report a constellation of cervical polyneuropathies in a patient treated with concurrent bortezomib, cetuximab, and cisplatin alongside intensity modulated radiotherapy for carcinoma of the tonsil with neck metastasis. The described deficits include brachial plexopathy, cervical sensory neuropathy, and oculosympathetic, recurrent laryngeal, and phrenic nerve palsies within the ipsilateral radiation field. Radiation neuropathy involving the brachial plexus is typically associated with treatment of breast or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In another case published in the literature, unilateral cervical polyneuropathies, including phrenic nerve palsy, developed in a patient who was given simultaneous bortezomib, cetuximab, and radiotherapy for head and neck cancer. 10 However, the neuropathies described in this case report could not be attributed to acute bortezomib toxicity; because bortezomib-related neuropathies typically occur during treatment and are reversible. 2,11 Sequelae neuropathies in the patient presented in this case showed that bortezomib neurotoxicity potentiates or is potentiated by concomitant radiotherapy and/or EGFR inhibition effect.…”
Section: Discussionmentioning
confidence: 66%
“…In another case published in the literature, unilateral cervical polyneuropathies, including phrenic nerve palsy, developed in a patient who was given simultaneous bortezomib, cetuximab, and radiotherapy for head and neck cancer. 10 However, the neuropathies described in this case report could not be attributed to acute bortezomib toxicity; because bortezomib-related neuropathies typically occur during treatment and are reversible. 2,11 Sequelae neuropathies in the patient presented in this case showed that bortezomib neurotoxicity potentiates or is potentiated by concomitant radiotherapy and/or EGFR inhibition effect.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, we found significant differences and correlations between high-and lowrisk patients with high sensitivity to drugs, such as Bortezomib_1191, Luminespib_1559, and Rapamycin_1084, suggesting that these three drugs may be used in the treatment of high-risk CESC patients. Previous studies found that Bortezomib was indeed effective in the treatment of CESC patients [61][62][63][64]. In combination therapy, Bortezomib significantly increases the sensitivity of multiple agents to CESC [61][62][63][64].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies found that Bortezomib was indeed effective in the treatment of CESC patients [61][62][63][64]. In combination therapy, Bortezomib significantly increases the sensitivity of multiple agents to CESC [61][62][63][64]. The mechanistic target of Rapamycin (mTOR) is an atypical serine/threonine kinase that plays an important role for several cancers, including cervical cancer [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…For head and neck tumors, bortezomib does not significantly inhibit proliferation-related pathways, such as STAT3, and has no significant effect on the expression of EGFR; therefore, it has poor efficacy in HNSCC in drug experiments and clinical applications [27,28]. Nevertheless, the role of PIs in the treatment of other tumors still provides new thinking for the treatment of head and neck tumors, and some studies are currently underway [29][30][31]. This study, for the first time, elucidated the effect of proteasome inhibition on the UPP and PSMB8 in laryngeal and hypopharyngeal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%